An efficient protocol of potato virus A eradication by thermotherapy coupled with in vitro culture of potato (Solanum tuberosum) - LI, YANLIN; HE, CHANGZHENG; HU, XINXI; LIU, MINGYUE; ZHOU, QING; XIONG, XINGYAO (The Indian Journal of Agricultural Sciences, 2016)
With the aim of developing an effective protocol for virus elimination from potato (Solanum tuberosum L.) plantlets, thermotherapy coupled with isolating the first nodal cuttings by in vitro culture was successful to potato virus A (PVA) elimination. The survival ratio of potato plantlets was affective by thermotherapy temperatures and durations. The optimal thermotherapy temperature was 36±1 oC with highest survival ratio and effective elimination. The results of RT-PCR indicated that the regenerated plantlets obtained from the first cycle (four weeks) of thermotherapy in daytime at 36±1 oC with light intensity 40 mmole/m/s for 12 hr, and 20±1 oC in darkness for 12 hr had PVA infected. While isolated the first nodal cuttings and followed by thermotherapy at the first cycle conditions for another two weeks, the PVA could be eliminated. Thermotherapy was given by culturing the nodal cutting from the infected of PVA for six weeks in total on MS medium, and the PVA-free plantlets were obtained. In concluded that the protocol of thermotherapy coupled with isolating the first nodal cuttings by in vitro culture in the study can be effectively used for virus free plantlets in potato, and probably also for other vegetable propagated plant species.